Index of Economic Freedom, case of Czech Republic - Shrbený, Filip; Stroukal, Dominik, 1987-; Máslo, Lukáš Augustin, 1985-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2017)
We have identified number of possible advices for the Czech Republic to improve its rating for both Heritage Foundation and Fraser Institute Economic Freedom Index, which often leads to top 10 countries in the world. These advices range from cuts in government spending, betterment in judicial system, to the establishing healthier environment for startups and advices to combat corruption. We further noticed some divergence between above mentioned indexes and managed to evaluate those indexes, which showed the simplicity yet usefulness of Heritage EFI and flexibility and sensitivity of the Fraser EFI. Weak sides of the research were noted and ideas for further research were given.
Vedoucí práce: Dominik Stroukal
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses